The theoretical gaps on the it productivity paradox: a conceptual paper / Amri Mohamad and Yuserrie Zainuddin - Mohamad, Amri; Zainuddin, Yuserrie (2015)
Basically the theoretical gaps are concentrated on the issue that focusing solely on the financial measurements to measure the firms' performance. It has been found that IT investment will bring not only financial benefits, but also nonfinancial benefits to the firms. The objective of this study is to investigate the relationship between information technology (IT) investment and the Malaysian Electrical and Engineering (E&E) manufacturing firms' performance. In addition, this paper also aims to establish the problem statement in the IT productivity paradox area that will serve as a basis for future research with regards to this issue within the E&E manufacturing performance in Malaysia.